2017
DOI: 10.1681/asn.2016121331
|View full text |Cite
|
Sign up to set email alerts
|

Association Analysis of the MHC in Lupus Nephritis

Abstract: Lupus nephritis (LN) is one of the most prevalent and serious complications of SLE, with significant effects on patient and renal survival. Although a large number of genetic variants associated with SLE have been identified, biomarkers that correlate with LN are extremely limited. In this study, we performed a comprehensive sequencing analysis of the whole MHC region in 1331 patients with LN and 1296 healthy controls and validated the independent associations in another 950 patients with LN and 1000 controls.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…A comprehensive sequencing analysis of the whole MHC region of a large LN cohort showed that HLA-DRB1 amino acid 11 is one of the five functional risk variants for LN within MHC regions. These independent risk variants also suggest that the risk of development of LN could be due to aberration in peptide presentation by MHC class 1 and 2 molecules to T cells and sex hormone dysregulation ( 75 ). Another source presumed that three amino acid positions (11, 13, and 26) located at the HLA-DRB1 epitope-binding groove establish a pathogenic structure in LN patients ( 76 ).…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive sequencing analysis of the whole MHC region of a large LN cohort showed that HLA-DRB1 amino acid 11 is one of the five functional risk variants for LN within MHC regions. These independent risk variants also suggest that the risk of development of LN could be due to aberration in peptide presentation by MHC class 1 and 2 molecules to T cells and sex hormone dysregulation ( 75 ). Another source presumed that three amino acid positions (11, 13, and 26) located at the HLA-DRB1 epitope-binding groove establish a pathogenic structure in LN patients ( 76 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alleles at the same HLA locus, which may differ structurally by a few nucleotides, can result in completely different disease susceptibility or resistance profiles (Xue et al, 2018). This explains the differential expression of the four HLA genes we identified in the SLE and LN datasets, with genetic polymorphisms resulting in systemic and local pathological changes (Xu et al, 2017). IRF8 is a member of the interferon regulatory factor (IRF) family that regulates the signaling pathway for Toll-like receptors (Salem et al, 2020).…”
Section: Disscussionmentioning
confidence: 92%
“…Several MHC haplotypes (HLA-DR2, HLA-DR3,and HLA-DR15) have been identified to increase the risk of SLE and lupus nephritis (Graham et al 2007;Chung et al 2014;Niu et al 2015). Until now, the role of these HLA molecules has been linked to comprised immune tolerance to nuclear autoantigens (Yellin et al 1997;Clynes et al 1998;Goodnow 2007;Xu et al 2017). However, studies suggest that epithelial cells such as podocytes and renal tubular cells also express HLA molecules and even regulate T cell activation (Wuthrich et al 1989;Frasca et al 1998;Banu and Meyers 1999;Yuan et al 2020).…”
Section: Lupus Nephritismentioning
confidence: 99%